2020
DOI: 10.37859/jsi.v3i1.1706
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Berkendara Selamat Dengan Kecelakaan Pengemudi Transportasi Roda Dua Berbasis Online Di Kota Pekanbaru

Abstract: Kecelakaan Lalu Lintas Jalan merupakan penyebab utama kematian dan cedera dan masalah kesehatan masyarakat yang meningkat secara global, mengakibatkan lebih dari 1,2 juta kematian setiap tahunnya. Lebih dari 62.000 orang tewas dalam kecelakaan lalu lintas yang melibatkan sepeda motor di 27 negara Uni Eropa antara tahun 2001 dan 2009. Kemajuan transportasi roda dua  berbasis online merupakan jawaban kebutuhan transportasi masyarakat saat ini, transportasi ini memberi kemudahan berupa masayarakat dapat menggunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…12 This study confirmed that implementing safety riding behavior was essential in reducing the risk of traffic accidents. 13 Based on previous studies, there was a relationship between unsafe workplace actions and accidents among online drivers and base drivers in Manado, with a significance level of (0.002). 14 Furthermore, a study in 2019 also showed a relationship between driver behavior and accidents among drivers in Bitung, with a significance level of (0.04).…”
Section: Discussionmentioning
confidence: 99%
“…12 This study confirmed that implementing safety riding behavior was essential in reducing the risk of traffic accidents. 13 Based on previous studies, there was a relationship between unsafe workplace actions and accidents among online drivers and base drivers in Manado, with a significance level of (0.002). 14 Furthermore, a study in 2019 also showed a relationship between driver behavior and accidents among drivers in Bitung, with a significance level of (0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Productive age is the age span of a person who can produce something, where he is in the peak phase of his activity and is active in looking for sources of income to support and improve the welfare of his family 12 Research by Tanriono, Doda, and Manampiring in 2019 found that a factor that has an important influence on the work accidents of motorcycle taxi drivers in Bitung is work fatigue that is not realized by motorists or often called the silent killer 14 . In addition, according to research conducted by Ruzain et al, (2020) regarding the correlation of safe driving knowledge with onlinebased two-wheeled transportation driver accidents in Pekanbaru City, it also found a significant correlation between safe driving knowledge and online-based twowheeled driver accidents 15 .…”
Section: Introductionmentioning
confidence: 87%
“…Hal ini dikarenakan, mereka yang pernah mengalami cedera pada saat berkendara sepeda motor akan belajar lebih tentang berkendara yang aman. Studi lain menunjukkan terdapat hubungan signifikan antara pengetahuan berkendara yang aman dengan kejadian kecelakaan lalu lintas (Ruzain, Herawati, & Christofa, 2020). Pengalaman mereka cedera, dapat menjadikan pelajaran tersendiri bagi pengendara.…”
Section: Pembahasanunclassified